PKM: improving the posyandu elderly capacity to improve the degree of elderly health - Suarmini, Kadek Ayu; Bukian, Putu Agus Windu Yasa; Megaputri, Putu Sukma; Dewi, Ni Kadek Nadia Sintia (Talenta Publisher, 2019)
Kubutambahan and Bulian Village are two villages that are included in the working area of the Primary health care in Kubutambahan. Integrated Healthcare Center (IHC) elderly in these two villages still have lower coverage than other villages. In addition, the elderly IHC cadre are also not very active in promoting activities and inviting all elderly elements in the villages of Bulian and Kubutamabahan to come to the IHC. The elderly exercise becomes innovative as an improvement in the quality of life of the elderly. In view of the need for active cadres so that elderly gymnastic instructors are not only trained by health workers but also by elderly IHC cadres themselves. The method used is application technology with three patern (promotion, information and education). The stages of implementation are preparation, implementation and evaluation. The target is for all the elderly in the working area of the health center. The results of this service include the provision of IHC information through loudspeakers car, cadre training, provision of additional food as a reward for the arrival of the elderly to the IHC, providing health information and elderly exercise. This service is effectively carried out so that there is an increase in elderly visits and elderly cadres become trained. In addition, the elderly cadre also developed themselves by becoming an elderly gymnastic instructor. The conclusion is that there is an increase in elderly visits and cadres are increasingly trained.